On Powers and Roots of Split Octonions - Mücahit Akbıyık (Journal of Mathematics)
In this article, we obtain the polar forms for two types of split octonions. We calculate De Moivre’s formulas for all polar forms of split octonions. Thus, we give the nth− powers and roots of split octonions and the matrix representation of split octonions. In addition, we present an illustrative example with Matlab codes.